MODERNISASI PENDIDIKAN AGAMA ISLAM PERSPEKTIF AS’AD SYAMSUL ARIFIN - Chanifudin Chanifudin; Luqman Bin Haji Abdullah (IAIN Ponorogo, 2022)
Abstract This study discusses the modernisation of Islamic Religiuos Education by As'ad Syamsul Arifin in Risalah Tauhid book. The book has introduced the teachings of the ash'ariyah-al-maturidiyah creed and introduced attitudes and behavior as a dynamic servant in filling life with various works that benefit the community. There are three objectives in this study, firstly, to examine the concept of monotheism of As'ad Syamsul Arifin, secondly, to examine the educational values contained in the Risalah Tauhid book and thirdly to correlate the monotheistic thinking of Kiai As'ad Syamsul Arifin to the modernization of Islamic religious education. This research is a literature study using a philosophical historical approach using content analysis methods and concepts in analyzing. The results of the study concluded that the first thought of As'ad Syamsul Arifin's monotheism was influenced by his lineage background, social environment and intellectual journey. The concept of the monotheism trilogy of Kiai As'ad Syamsul Arifin rububiyah, tawhid uluhiyah, and tawhid asma wa siffat, is different from the three concepts of monotheism of Wahhabism. Whereas rububiyah and uluhiyah are an inseparable unit and introduce the Asy'ariyah-Al-Maturidiyah creed into a progressive creed; Second, As'ad Syamsul Arifin uses monotheism as the foundation of all worship, both direct worship to Allah S.W.T and social worship. Education becomes the spirit in building educational values with the nuances of monotheism; The three Asy'ariyah beliefs are the driving force for modernizing religious education. The ability to transform education from conservative to liberal is As'ad's ability to understand the meaning of